Representation of Russia in the British online sources in 2022 - Alexander V. Sharikov (RUDN Journal of Studies in Literature and Journalism)
The article examines peculiarities of representation of russia in British online sources in 2022, when russia launched a special military operation in ukraine. the author used a statistical approach to analysis based on the factiva monitoring system, the database of which contains about 4.5 million texts published on 416 British online resources from January 1 to december 31, 2022 at both national and regional levels. sentiment analysis (factiva version) was used to determine the tone of the messages. the analysis showed that in 2022, russia ranked fourth in terms of number of articles with its mention in the analyzed corpus of texts, the first being the united Kingdom itself, the second, the united states, and the third, ukraine. from the point of view of the agenda-setting theory (mcCombs, shaw), this fact indicates the high importance of russia for the uK media. most often, materials mentioning russia on British online resources in 2022 were published by the national editions of “the financial times”, “the independent” and “the times”. at the regional level, the largest number of text materials mentioning russia was found: in england - on the website of the radio station “City am online”; in northern ireland - on the website of “lurgan mail”; in Wales - on the website of “the Western mail”; in scotland - on the portal “thescottishsun.co.uk”. the British media were more focused on covering the non-military aspects of the russian-ukrainian conflict, mainly, on political and economic problems. In general, the neutral tone of this set of materials prevailed, that is explained by the absolute dominance of short non-evaluative information messages in it. This is true for both national and regional publications. At the same time, materials of a negative tone prevail over positive ones when it comes to Russia. A difference was found in the intensity of negative coverage of Russia in national and regional online sources in the UK. The most rigid position is taken by national British sources. Among the regional ones, the negative focus on online resources in England is greater, and sources in Scotland and Northern Ireland show the least negative tone.